ANALISIS PENGARUH GROWTH, SIZE, EVA DAN VARIABEL MAKROEKONOMI TERHADAP PERUBAHAN LABA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - seno hadi saputro (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2018)
This research is perform to evaluate the influence of Growth, Size, BI Rate, Inflation and EVA toward the changes in profit. Methodology research as the sample used purposive sampling and this research in manufacturing company listed in BEI period 2008-2016. Data analysis with multiplier regression of random effect datapanel method. The results obtained are the empirical evidence of analysis show as growth and BI Rate not influence toward the changes in profit of manufacturing company. Size and Inflation have a negative influence toward the changes in profit of manufacturing company and Economic Value Added have a positif influence toward the changes in manufacturing company. Keyword : Growth, Size, Eva, Macroeconomic, The changes in profit